Late Miocene landform construction in east-southern Tibet: seismic evidence and a synthetic review - Xiang, Bo; Xu, Xiao; Yu, Jiahao; Guo, Xiaoyu; Wu, You; Li, Chunsen; Wu, Jiajie; Tong, Xiaofei; Luo, Xucong (Frontiers in Earth Science, 2023)
The north-south striking landform perpendicular to the dominant collision zone between the Indian and Eurasian plates was constructed in east-southern Tibet (EST) during the Late Miocene. The building processes remain ambiguous, partly owing to the lack of recognition of crustal-scale architecture. Here we deployed an east-west-oriented 120 km-long short-period dense array across the northwestern corner of EST. Results from P-wave receiver functions show a mid-crustal ductile detachment atop the crystalline basement of the eastern Lhasa terrane that has displaced the overlying crust including the upper part of the Yardong-Gulu Rift (YGR) eastward for about 100 km and an offset Moho geometry left behind beneath the Nyainqentanghla Range. Combined previous studies on the vertical heterogeneity in crustal strength beneath the YGR, a synthetic view implies a decoupled crustal architecture of EST to respond the dynamic interactions between the eastward extrusion of the Tibetan Plateau and the northward penetration of the Indian plate that constitutes the Eastern Himalayan Syntaxis. The integrated processes eventually brought active landform construction in the plateau's interior and partly contributing to the contemporaneous intensification of monsoon in SE Asia.